Caveolin-1 Alters the Pattern of Cytoplasmic Ca(2+) Oscillations and Ca(2+)-dependent Gene Expression by Enhancing Leukotriene Receptor Desensitization - Yeh, Yi-Chun (American Society for Biochemistry and Molecular Biology, 2014)
Cytoplasmic Ca(2+) oscillations constitute a widespread signaling mode and are often generated in response to stimulation of G protein-coupled receptors that activate phospholipase C. In mast cells, repetitive Ca(2+) oscillations can be evoked by modest activation of cysteinyl leukotriene type I receptors by the physiological trigger, leukotriene C(4). The Ca(2+) oscillations arise from regenerative Ca(2+) release from inositol 1,4,5-trisphosphate-sensitive stores followed by Ca(2+) entry through store-operated Ca(2+) channels, and the latter selectively activate the Ca(2+)-dependent transcription factor NFAT. The cysteinyl leukotriene type I receptors desensitize through negative feedback by protein kinase C, which terminates the oscillatory Ca(2+) response. Here, we show that the scaffolding protein caveolin-1 has a profound effect on receptor-driven Ca(2+) signals and downstream gene expression. Overexpression of caveolin-1 increased receptor-phospholipase C coupling, resulting in initially larger Ca(2+) release transients of longer duration but which then ran down quickly. NFAT-activated gene expression, triggered in response to the Ca(2+) signal, was also reduced by caveolin-1. Mutagenesis studies revealed that these effects required a functional scaffolding domain within caveolin-1. Mechanistically, the increase in Ca(2+) release in the presence of caveolin-1 activated protein kinase C, which accelerated homologous desensitization of the leukotriene receptor and thereby terminated the oscillatory Ca(2+) response. Our results reveal that caveolin-1 is a bimodal regulator of receptor-dependent Ca(2+) signaling, which fine-tunes the spatial and temporal profile of the Ca(2+) rise and thereby its ability to activate the NFAT pathway.